National programme for prevention of burn injuries - Gupta J; Makhija L; Bajaj S (Indian Journal of Plastic Surgery)
The estimated annual burn incidence in India is approximately 6-7 million per year. The high incidence is attributed to illiteracy, poverty and low level safety consciousness in the population. The situation becomes further grim due to the absence of organized burn care at primary and secondary health care level. But the silver lining is that 90% of burn injuries are preventable. An initiative at national level is need of the hour to reduce incidence so as to galvanize the available resources for more effective and standardized treatment delivery. The National Programme for Prevention of Burn Injuries is the endeavor in this line. The goal of National programme for prevention of burn injuries (NPPBI) would be to ensure prevention and capacity building of infrastructure and manpower at all levels of health care delivery system in order to reduce incidence, provide timely and adequate treatment to burn patients to reduce mortality, complications and provide effective rehabilitation to the survivors. Another objective of the programme will be to establish a central burn registry. The programme will be launched in the current Five Year Plan in Medical colleges and their adjoining district hospitals in few states. Subsequently, in the next five year plan it will be rolled out in all the medical colleges and districts hospitals of the country so that burn care is provided as close to the site of accident as possible and patients need not to travel to big cities for burn care. The programme would essentially have three components i.e. Preventive programme, Burn injury management programme and Burn injury rehabilitation programme.